2016
DOI: 10.1016/j.canep.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers, aspirin, and risk of colorectal cancer: Findings from the physicians’ health study

Abstract: Background Chronic inflammation has been implicated in colorectal carcinogenesis. However, the associations between plasma inflammatory markers and risk of colorectal cancer have been inconsistent. Methods In a nested case-control study in the Physicians’ Health Study, we prospectively investigated the associations of plasma C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor receptor 2 (TNFR-2) with risk of colorectal cancer, and whether aspirin modified these associations among 268 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…No association was seen in the meta-analysis between fibrinogen and CRC risk (409 cases, Figure 2f), but a positive association has been reported in two prospective studies that used HR as risk measure [76,94]. Only one [32] out of six [28,32,34,51,74, 87] studies (some using HR while others OR) on IL-6 and CRC reported a positive association with OR=1.76 (95%CI 1.01-3.06). All other inflammatory parameters were examined in less than 4 studies.…”
Section: Colorectal Cancermentioning
confidence: 91%
“…No association was seen in the meta-analysis between fibrinogen and CRC risk (409 cases, Figure 2f), but a positive association has been reported in two prospective studies that used HR as risk measure [76,94]. Only one [32] out of six [28,32,34,51,74, 87] studies (some using HR while others OR) on IL-6 and CRC reported a positive association with OR=1.76 (95%CI 1.01-3.06). All other inflammatory parameters were examined in less than 4 studies.…”
Section: Colorectal Cancermentioning
confidence: 91%
“…Their study showed that plasma inflammatory indicators, which include CRP, have not been significantly linked to CRC risk in men and that the null relationship between plasma CRP level and CRC risk noted in this research is consistent with the majority of prior research by. 18 In contrast, in 19 of their studies, they found that CRP levels are increased in those with CRC and that inflammation is a risk factor for the progression of colon cancer in people at average risk.…”
Section: Discussionmentioning
confidence: 93%